Introduction: minerals to metal-organic frameworks. (27th May 2019) - Phillips, Anthony E.
Abstract : Mineralogy and materials design have always been closely intertwined. Here, I review some of the earliest work in modern materials chemistry to explicitly take inspiration from mineral structures and properties, and introduce the invited contributions to this theme issue. This article is part of the theme issue 'Mineralomimesis: natural and synthetic frameworks in science and technology'.